Perception and Behavior of Farmers Towards the Use of Organic Fertilizers in Rice Plants in Kewayuhan Village, Pejagoan District, Kebumen Regency - Ngafiful Furqon; Rennanti Lunnadiyah Aprilia (Asosiasi Dosen Muda Indonesia, 2026)
The application of organic fertilizer is an important strategy for supporting sustainable rice farming by improving soil fertility, maintaining soil quality, and reducing dependence on synthetic fertilizers. However, the adoption of organic fertilizer among rice farmers remains relatively limited, indicating the need to understand the behavioral factors influencing its utilization. Objective: This study aimed to analyze farmers’ perceptions and behavior regarding organic fertilizer use and to examine the relationship between farmers’ perceptions and organic fertilizer utilization behavior in rice cultivation in Kewayuhan Village, Pejagoan District, Kebumen Regency. Methodology: This study employed a quantitative descriptive design with a survey approach. Data were collected from 79 rice farmers selected through simple random sampling from a population of 380 active farmers. A structured questionnaire was used as the research instrument. The data were analyzed using descriptive statistics, validity and reliability testing, and Spearman Rank correlation analysis. Findings: The results showed that farmers generally had positive perceptions of organic fertilizer, with 51.9% of respondents classified as having a high level of perception. Farmers’ behavior toward organic fertilizer utilization was also relatively favorable, although inconsistencies remained in application dosage, frequency, and continuity. The correlation analysis indicated positive associations between farmers’ perceptions and organic fertilizer utilization behavior, suggesting that more favorable perceptions tend to encourage better implementation of organic fertilizer practices. Implications: The findings indicate that improving farmers’ perceptions and knowledge should be accompanied by continuous agricultural extension, technical assistance, improved fertilizer availability, and stronger institutional support. These efforts are expected to increase the consistency of organic fertilizer application and support sustainable fertilizer management in rice farming. Originality: The originality of this study lies in integrating the cognitive, affective, and conative dimensions of farmers’ perceptions and examining their relationship with organic fertilizer utilization behavior using a non-parametric correlation approach. This study also provides specific empirical evidence from rice farmers in Kewayuhan Village, an area that has received limited attention in previous organic fertilizer adoption studies.